Land water contribution to sea level from GRACE and Jason‐1measurements. Issue 1 (28th January 2013) - Jensen, L.; Rietbroek, R.; Kusche, J.
Abstract: [1] We investigate the effect of water storage changes in the world's major hydrological catchment basins on global and regional sea level change at seasonal and long‐term time scales. In a joint inversion using GRACE and Jason‐1 data, we estimate the time‐dependent sea level contributions of 124 spatial patterns ("fingerprints") including glacier and ice sheet melting, thermal expansion, changes in the terrestrial hydrological cycle, and glacial isostatic adjustment. Particularly, for hydrological storage changes, we derive fingerprints of the 33 world's largest catchment basins, assuming mass distributions derived from the leading EOFs of total water storage in the WaterGap Global Hydrological Model (WGHM). From our inversion, we estimate a contribution of terrestrial hydrological cycle changes to global mean sea level of − 0.20 ± 0.04 mm/yr with an annual amplitude of 6.6 ± 0.5 mm for August 2002 to July 2009. Using only GRACE data in the inversion and comparing to hydrological changes derived from GRACE data directly using a basin averaging method shows a good agreement on a global scale, but considerable differences are found for individual catchment basins (up to 180%). Hydrological storage change estimates in 33 basins from the GRACE/Jason fingerprint inversion indicate a trend 46% smaller and an annual amplitude 43% bigger compared to WGHM‐derived storage changes. Mapping the hydrological trends to regional sea level reveals the strongest sea level rise along the coastlines of South America (max 0.9 mm/yr) and West Africa (max 0.4 mm/yr), whereas around Alaska and Australia, we find the hydrological component of sea level falling (min −2.0 mm/yr and −0.9 mm/yr). Abstract : Weekly GRACE and Jason‐1 data are jointly inverted in a "fingerprint" approach The total water storage in the 33 world's largest watersheds is analyzed Hydrological cycle changes induce a sea level change of −0.20 ± 0.04 mm/yr